Shaping the Living Body: paradigms of soma and authority in Thomas Hanna’s writings - Giorgi (Università di Bologna, Bolonha, Italy) Margherita De (Revista Brasileira de Estudos da Presença, 2022)
This article outlines some features of the discursive strategies adopted by Thomas Hanna in order to legitimate Somatics – as well as his own method – in the eyes of the scientific community. The notion of soma and the representations of its functions will be recognized at the core of this issue. In order to stress the enduring risk of dogmatism of the scientific rhetoric to our days, as well as their influence on the configuration of somatic discourses, I will be mainly referring to Isabelle Ginot’s radical epistemology and Martha Eddy’s critical perspective.